La puntuación y las unidades textuales: una perspectiva discursiva para el estudio de los problemas de su uso y para su enseñanza - Sánchez Avendaño, Carlos (2011)
This article presents a detailed analysis concerning textbooks for the teaching of punctuation as well as punctuation marks used by university students. The analysis is carried out within a discursive perspective.